2013
DOI: 10.1088/0004-637x/767/1/94
|View full text |Cite
|
Sign up to set email alerts
|

A 1.1-1.9 GHz SETI SURVEY OF THEKEPLERFIELD. I. A SEARCH FOR NARROW-BAND EMISSION FROM SELECT TARGETS

Abstract: We present a targeted search for narrow-band (< 5 Hz) drifting sinusoidal radio emission from 86 stars in the Kepler field hosting confirmed or candidate exoplanets. Radio emission less than 5 Hz in spectral extent is currently known to only arise from artificial sources. The stars searched were chosen based on the properties of their putative exoplanets, including stars hosting candidates with 380 K > T eq > 230 K, stars with 5 or more detected candidates or stars with a super-Earth (R p < 3 R ⊕ ) in a > 50 d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 27 publications
1
154
0
Order By: Relevance
“…This type of signal is of particular interest in traditional SETI projects because it is too narrow to arise naturally from known natural astrophysical sources, and represents a power-efficient method of transmitting a beacon signal out to great distances. Given the relatively short distances to our targets, we are able to neglect the various interstellar distortions (Cordes et al 1997;Siemion et al 2013, e.g., scintillation in time and frequency, spectral broadening). We note that our observation planning system requires that observed targets be sufficiently far away from the Sun to allow us to neglect any spectral broadening due to the interplanetary medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of signal is of particular interest in traditional SETI projects because it is too narrow to arise naturally from known natural astrophysical sources, and represents a power-efficient method of transmitting a beacon signal out to great distances. Given the relatively short distances to our targets, we are able to neglect the various interstellar distortions (Cordes et al 1997;Siemion et al 2013, e.g., scintillation in time and frequency, spectral broadening). We note that our observation planning system requires that observed targets be sufficiently far away from the Sun to allow us to neglect any spectral broadening due to the interplanetary medium.…”
Section: Discussionmentioning
confidence: 99%
“…Another solution would be to collapse the data to a lower frequency resolution before applying the tree summation in the algorithm (Siemion et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radio SETI observations started with Drake (1961) who searched for narrow-band linesand have continued to the present day with increasing levels of sophistication. For instance, Siemion et al (2013) recently searched for interplanetary radar signals in multi-planet systems during conjunctions, 11 and established that 1% of transiting exoplanet systems host civilizations that emit narrow-band radiation in the 1-2 GHz band with an equivalent isotropically radiated power (EIRP) of ∼1.5×10 13 W. Whether ETI would set up beacons for the benefit of curious radio astronomers in other civilizations is unknown, but setting up such beacons is the best possible way to advertise our presence in the universe. Radio emission is energetically, and hence, economically inexpensive to generate.…”
Section: Setimentioning
confidence: 99%
“…There is at least one Galactic-origin theory (that also predicts pulse repetition) wherein these bursts originate in flare stars, and are dispersed by the stellar corona (Loeb et al 2014). A resolution of the mystery has been made complicated by two recent discoveries, namely, that of FRB 150418, which has been claimed to be 11 Note the error in the sensitivity calculation in Siemion et al (2013)and the values reported in their 12 https://sites.google.com/site/publicsuperb/ associated with a slow radio transient in an elliptical galaxy interpreted to be an afterglow of a cataclysmic, non-repeating event (Keane et al 2016), and that of FRB 121102,which has been shown to repeat (Spitler et al 2014. 13 Eighteen FRBs have been reported in thepublished literature 14 ).…”
Section: Fast Radio Burstsmentioning
confidence: 99%